Plant flavonoids as inhibitors of calcium oxalate urolithiasis - Sahabudin, R.M. Sahabudin; Noor Ahmad, Mohd.; Sirajinisa, H.M.; Temumeni, A. (Malaysian Journal of Science, 1999)
Flavonoids, including flavones, flavonol and their glycosides, showed inhibitory activity on the growth of calcium oxalate crystals. Kaempferol and luteoline exhibited the highest inhibitory activity among the nine flavonoids studied. Results on the monitoring of the urine of patients suffering from kidney stones who were given meshed juice of Raphanus sativus are promising, and studies are on-going for a larger sample population.